ANALISIS PELAKSANAAN SISTEM DAN PROSEDUR AKUNTANSI PENGELUARAN KAS PADA DINAS KESEHATAN KOTA MANADO - Laotongan, Ray Risiano Imanuel; Saerang, David P. E.; Wokas, Heince R. N. (ACCOUNTABILITY, 2015)
Cash expenditures is a component that is very important resource in the implementation of development programs that have been planned by the government. In government department cash expenditure have system and procedure that manage/control the cash expenditure. The purpose of this research was to analyze if the implementation of systems and procedures for cash expenses appropriate with the existing rule. Objects of this research is on the Department of Public Health of Manado City. Anlysis method used is descriptive analysis method that aims to make a picture of systematic, factual, and accruals of the facts, by comparing between system and expenses procedures performed by the Department of Public Health with the concepts of cash expenses system.The result of this research about system and procedure at the Department of Public Health of Manado City, cash expenditure procedure was appropriate with the existing rules but in the implementation still have a shortage that there is no authorization through PPK-SKPD.